Kontribusi Media dalam Memenuhi Kebutuhan Beragama Perempuan Pekerja Seks Komersial di Lokalisasi Lorong Indah - Khoirunnida, Fatma Laili; Sa'diyah, Zaimatus; Farihah, Irzum; Susilowati, Retno (FIKRAH, 2017)
This article aims to reveal the social phenomenon of prostitution in Lorong Indah Pati. As a human, especially a religious person, commercial sex workers have the right to seek meaningful living. This research uses qualitative approach with data collection technique through observation, interview and documentation. Informants in this study are commercial sex workers in the Localization of Lorong Indah Pati, religious leaders and the surrounding community. The results show that the process of searching meaning in life in order to maintain the existence of religious needs remains the latent side behind the vulgar display of commercialization of their bodies. That religion gave birth to a pattern of searching for different meanings of life for commercial sex workers. Among other things, the use of the media, television and radio as well as print media (newspaper) as one of the instruments that have an important role to meet the needs of community religion in the community of PSK in Lorong Indah Pati